Mechanisms involved in biocontrol and plant induced resistance by Trichoderma asperellum (T. harzianum T-203) - Chet I; Shoresh M; Yedidia I; Viterbo A (浙江大学学报. 农业与生命科学版)
Growing awareness of the environmental damage caused by the use of chemical substances for plant disease control in agriculture has raised the need to study biological alternatives, such as activating the defense response of plant crops by inducers not toxic to the environment. Trichoderma spp. are effective biocontrol agents for a number of soilborne pathogens, and are also known for their ability to enhance plant growth and to induce systemic resistance (ISR) in plants.In our laboratory we are studying the mechanism of induction of systemic responses against angular leaf spot disease of cucumber-Pseudomonas syringae pv. lachrymans (Psl), following application of T. asperellum to the root system. The protection afforded by the biocontrol agent is associated with concomitant accumulation of secondary metabolites of a phenolic nature and mRNA of two defense genes: the phenylpropanoid pathway gene phenylalanine ammonia lyase (PAL) and the octadecanoid pathway gene hydroxyperoxide lyase (HPL). Combining gene expression analysis, measurements of signal molecules levels and use of specific hormone inhibitors we could demonstrate that the JA/ethylene signaling pathway is involved in the systemic response induced by Trichoderma.A molecular analysis of Trichoderma genes and proteins differentially induced by root interaction reveals that molecules related to phytopathogenicity, but also known as elicitors of plant defense responses, are transiently activated in planta, enabling at the same time intracellular colonization and induction of systemic defense responses pathways.It appears that Trichoderma as a beneficial soil fungus has several efficient modes of action.